If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2t + 3) = -35 Reorder the terms: -7(3 + 2t) = -35 (3 * -7 + 2t * -7) = -35 (-21 + -14t) = -35 Solving -21 + -14t = -35 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -14t = -35 + 21 Combine like terms: -21 + 21 = 0 0 + -14t = -35 + 21 -14t = -35 + 21 Combine like terms: -35 + 21 = -14 -14t = -14 Divide each side by '-14'. t = 1 Simplifying t = 1
| s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 | | 2A+2b=bc | | f(2n+1)=f(n)+f(n-1) | | 6x-6=-15 | | (q-9)*4=8 | | (9c+5)(7c-1)=0 | | -10m-11m+13m=16 | | p(x)=2x^3+x^2-49x+8 | | (q-4)*9=8 | | 6j(j+4)=0 |